Rigidity results for closed vacuum static spaces - Guangyue Huang; Botao Wang (AIMS Mathematics, 2023)
In this paper we studied rigidity results for closed vacuum static spaces. By using the maximum principle, we achieved rigidity theorems under some pointwise inequalities and showed that the squared norm of the Ricci curvature tensor was discrete.